A review of current knowledge on Pollution, Cigarette Smoking and COVID-19 diffusion and their relationship with inflammation: Inflammation, pollution and Covid-19 - Gallo, Manuela; Street, Maria E; Guerra, Fabiola; Fanos, Vassilios; Marcialis, Maria Antonietta (Acta Biomedica Atenei Parmensis, 2020)
Coronavirus disease (COVID-19) is an infectious disease caused by the newly discovered coronavirus, Sars-Cov-2. This infection can cause mild to very severe respiratory and systemic illness mainly related with a cytokine storm. The epidemiology of COVID-19 is under continuous evolution, and studies are ongoing aiming at identifying the possible factors facilitating the diffusion of this infection. It is documented that air pollution and smoking are a leading cause of human morbidity and mortality globally, and can increase the risk of many diseases, including respiratory diseases. Overall, a linear relationship between exposure to atmospheric pollutants and diffusion of the Sars-Cov2 virus seems to exist. However, this correlation, cannot be regarded as a cause-effect relationship. The available data show that air pollution is responsible for inflammation and hyper-activation of innate immunity that are associated with the worst outcomes of covid-19 but do not allow to conclude that atmospheric particulate is responsible for increased contagion. As to smoking, nicotine activation of nicotinic receptors leads to enhanced protease activation, apoptosis and inflammatory signaling through the same pathways (Renin-angiotensin system (RAS) and angiotensin-converting enzyme 2 (ACE2)) used by the virus increasing the inflammatory/destructive action of the virus itself. The increase in non-communicable diseases and of chronic inflammatory diseases is in line with environmental pollution, related climate changes, and with an augmented susceptibility to infectious diseases with increased contagiousness and morbidity. Restrictive measures to limit environmental pollution are needed worldwide as this represents a threat for human health.